Combined Biopsy and Imaging-Guided Microwave Ablation by Using a Coaxial Guiding Needle - Yi-Wei Wu; Gabriel Chan; Ivan Kuang Hsin Huang; Justin Kwan; Gavin Hock Tai Lim; Lawrence Han Hwee Quek; Uei Pua (Journal of the Belgian Society of Radiology, 2021)
This article demonstrates the technique of using a coaxial guiding needle to perform combined percutaneous biopsy and microwave ablation via a single tract. From May 2019 to July 2020, 14 patients underwent combined biopsy and microwave ablation by using a coaxial guiding cannula. Tumors were in the kidney of six patients (43%), the liver of six patients (43%), and the lung in two patients (14%). The diagnostic yield of biopsy was 86% (12/14). Ablation technical success rate was 100%. In conclusion, using a coaxial guiding needle in microwave ablation and biopsy is safe and effective.